2017
DOI: 10.1111/dgd.12405
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule array observed in the posterior‐vegetal cortex during cytoplasmic and cortical reorganization of the ascidian egg

Abstract: Body axis formation during embryogenesis results from asymmetric localization of maternal factors in the egg. Shortly before the first cleavage in ascidian eggs, cell polarity along the anteroposterior (A-P) axis is established and the cytoplasmic domain (myoplasm) relocates from the vegetal to the posterior region in a microtubule-dependent manner. Through immunostaining, tubulin accumulation during this reorganization is observable on the myoplasm cortex. However, more detailed morphological features of micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…As shown in Figure 4D and Supplemental Movie S6, the sperm aster, which was detected as a radially aligned CiEB1-mCherry bound to the vicinity of the plus end of microtubules, moved across the egg cortex during the cytoplasmic reorganization. Previous observations (Sardet et al, 1989;Roegiers et al, 1999;Ishii et al, 2017) have revealed that after the initial phase of ooplasmic segregation, the sperm aster moves to the posterior-vegetal hemisphere along the A-V axis. The movement of the sperm aster in Figure 4D suggested that the alignments of F-actin that we observed in the vegetal hemisphere were normal to the A-V axis.…”
Section: The Direction Of Intracellular Ca 2+ Waves Correlates With the Cell Polarity Of Fertilized Ciona Eggsmentioning
confidence: 90%
See 1 more Smart Citation
“…As shown in Figure 4D and Supplemental Movie S6, the sperm aster, which was detected as a radially aligned CiEB1-mCherry bound to the vicinity of the plus end of microtubules, moved across the egg cortex during the cytoplasmic reorganization. Previous observations (Sardet et al, 1989;Roegiers et al, 1999;Ishii et al, 2017) have revealed that after the initial phase of ooplasmic segregation, the sperm aster moves to the posterior-vegetal hemisphere along the A-V axis. The movement of the sperm aster in Figure 4D suggested that the alignments of F-actin that we observed in the vegetal hemisphere were normal to the A-V axis.…”
Section: The Direction Of Intracellular Ca 2+ Waves Correlates With the Cell Polarity Of Fertilized Ciona Eggsmentioning
confidence: 90%
“…The initial cytoplasmic reorganization occurs immediately after the fertilization caused by the contraction of cortical actomyosin network (Jeffery and Meier, 1983;Jeffery, 1984;Sawada, 1983;Sawada andOsanai, 1984, 1985). The following reorganization of cytoplasm is driven by multiple microtubule systems that include sperm asters (Sawada and Schatten, 1988;Chiba et al, 1999;Ishii et al, 2017;Goto et al, 2019). Importantly, these cytoplasmic movements are critically important for the establishment of the body axes of the ascidian embryo during development (Nishida, 2005;Makabe and Nishida, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For microtubule staining, dechorionated Ciona eggs/embryos were fixed with 100% methanol at room temperature (approximately 25 °C) for 1 h. The fixed specimens were treated with ethanol up series (35%, 70%, and 100%) and stored at −30°C until further use. After washing with phosphate-buffered saline containing 0.05% Tween 20 (PBST), the specimens were treated with G1T0 (4 mol/L urea (MP Biomedicals, Santa Ana, CA, USA), and 1% glycerol in distilled water) for 90 min at 4 °C [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…Z-projections and the midplane optical sections are displayed with animal pole upward. The animal pole was defined based on the position of the meiotic apparatus, myoplasm configuration, or parallel direction of the CAMP [ 12 ]. All analyses were performed using the ImageJ software [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation